Modified slag fiber reinforced cement mortar and preparation method thereof

Through the combination of modified slag fiber and nano-silica sol, the problems of high brittleness and low bending strength of cement matrix composite materials are solved, and efficient fiber-reinforced cement mortar is achieved, with good engineering application prospects.

CN120328972APending Publication Date: 2025-07-18FUJIAN AGRI & FORESTRY UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510618234.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-14
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The existing cement-based composite materials have problems such as high brittleness, low flexural strength, and easy cracking. In addition, traditional fiber reinforced materials have high energy consumption, large carbon emissions and poor dispersion, making them difficult to widely use in engineering.

Method used

Modified slag fibers are used as reinforcement, and the slag fibers are modified by nano-silica sol to increase the surface roughness of the fibers and form a uniform C-S-H gel in the cement matrix, improving the binding ability between the fibers and the matrix, and using the high tensile strength of the slag fibers and the catalytic action of the nano-silica sols to promote the hydration reaction.

Benefits of technology

It significantly improves the flexural strength, split tensile strength and early strength of cement mortar, improves the toughness of the material, reduces brittleness, and provides better technical and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120328972A_ABST
    Figure CN120328972A_ABST
Patent Text Reader

Abstract

The invention discloses modified slag fiber reinforced cement mortar and a preparation method thereof. According to the invention, the modified slag fiber is adopted as a reinforcement body, and the method has the advantages of reasonable utilization of solid wastes, low energy consumption, low cost, environmental protection, high mechanical properties of a mortar test piece, small shrinkage cracking and the like. The nano silica sol is adopted to modify the slag fibers, so that the durability of the slag fibers in a cement material can be better improved, hydration products on the surfaces of the fibers can be distributed more uniformly and densely, and an interface transition area between the fibers and a matrix material is reinforced, so that the strength of the mortar is remarkably improved; the used slag fiber is a fibrous material prepared by taking blast furnace slag and fly ash as raw materials through a blowing or centrifugal thread throwing process, so that the solid waste utilization rate can be increased, and environmental governance and protection are facilitated. According to the implementation of the invention, on one hand, the practical application of the slag fiber in the cement matrix material is explored; on the other hand, solid waste utilization can be promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of fiber - reinforced cement - based composites, and particularly relates to a modified slag fiber - reinforced cement mortar and a preparation method thereof. Background Art

[0002] Cement - based composites have the characteristics of high compressive strength, but also have defects such as high brittleness, low flexural strength, and easy cracking, thus restricting their application in some engineering fields. By adding various fibers, such as carbon fibers, glass fibers, polypropylene fibers, etc. to cement materials, their mechanical properties and crack - resistance can be significantly improved. Specifically, the fibers connecting the two ends of the crack will bear the tensile stress, thereby playing a role in inhibiting the crack propagation. The fiber - reinforced cement - based structure can ensure its normal working performance under strong load pressure and large deformation conditions. Only when the bonding force between the matrix and the fiber is damaged or the fiber reaches the ultimate load value of the tensile strength, the overall structure will be damaged. Therefore, the fiber - reinforced cement - based material has good tensile working performance, especially with a large improvement in toughness.

[0003] Currently, most of the fibers used in cement - based composites are synthetic fibers, which have disadvantages such as high energy consumption, large carbon emissions, and non - renewable in the production process. In addition, there are also some difficult - to - solve problems in their actual engineering applications. For example, it is difficult to mix and form steel fiber - reinforced cement - based composites, and they are prone to corrosion; carbon fibers are expensive and have poor dispersibility in the cement matrix; glass fibers have poor alkali - resistance and crack - resistance. Summary of the Invention

[0004] In view of the defects and problems existing in the above - mentioned background art, the present invention provides a modified slag fiber - reinforced cement mortar and a preparation method thereof.

[0005] To achieve the above object, the present invention adopts the following technical solutions: The present invention provides a modified slag fiber - reinforced cement mortar and a preparation method thereof. The raw material composition of the modified slag fiber - reinforced cement mortar includes modified slag fibers, cement, standard sand, and water. Among them, the modified slag fibers are obtained by modifying slag fibers with a modifier; among them, the modified slag fibers account for 0.3% of the mass of the cement, the modifier is nano - silica sol, and its mass fraction is 10% of the slag fibers; the mass ratio of cement, standard sand, and water is 1﹕0.75﹕0.4.

[0006] Furthermore, the preparation method of the modified slag fibers includes the following steps: (1) Utilize the property that slag fibers are uniformly dispersed in water. Immerse the agglomerated slag fibers in water, and use a high-speed shear machine (rotation speed 500 - 1000 r / min, time 1 - 3 min) to completely disperse and homogenize the slag fibers in water. This treatment process can also etch the surface of the slag fibers, increasing the surface roughness of the slag fibers without damaging their physical structure. (2) Spread the uniformly dispersed slag fibers flat on a sieve, drain the water, and place the slag fibers in an oven at 103 °C for drying for 2 h. (3) Spread the dried slag fibers flat on a tray. Take nano-silica sol, and use a nano-level atomizing sprayer to evenly spray the modifier nano-silica sol on the surface of the slag fibers to ensure full contact between the slag fibers and the modifier. Place the slag fibers sprayed with the modifier in an oven at 103 °C for drying for 4 h to obtain the modified slag fibers.

[0007] Further, the nano-silica sol is a transparent liquid, with SiO₂ solid content: 30 ± 1 wt%, Na₂O solid content: ≤ 0.3 wt%, and its physical property indexes are viscosity: 7 mPa·s, density: 1.21 - 1.29 g / cm 3 , particle size: 10 - 20 nm, pH value: 9 - 10.

[0008] Further, the slag fiber length is 3.9 - 7.0 mm, the diameter is 900 - 950 μm, the moisture content is 0.17%, and the slag ball content is 0.4%.

[0009] Further, the standard sand particle size is 0.08 - 1.6 mm, and the moisture content is 0.17%.

[0010] Further, the cement is composite Portland cement P.C 42.5.

[0011] Further, the preparation method of the modified slag fiber reinforced cement mortar includes: preparing the modified slag fibers, cement, and standard sand into a cementitious material in proportion, dry-mixing the component materials for 2 - 3 min, adding water and continuing to stir for 1 min after stirring evenly, placing the mortar in a mold, manually ramming it, and vibrating it on a vibrating table for molding; demolding after solidifying for 24 h, and placing the specimen in a standard constant temperature and humidity curing box for curing to obtain the modified slag fiber reinforced cement mortar specimen.

[0012] Further, the curing in the standard constant temperature and humidity curing box is specifically: curing in a standard constant temperature and humidity curing box with a relative humidity of 90 ± 5% and a temperature of 20 ± 5 °C for 28 d.

[0013] In the present invention, the slag fiber is provided by Fujian Dehua Dongxinbo New Material Technology Co., Ltd. It is a fibrous material prepared from blast furnace slag and fly ash as raw materials under the limitation of mass ratio through a blowing or centrifugal spinning process. It has a small density, a large specific surface area and aspect ratio, a high tensile strength, and good dispersibility compared with glass fiber, steel fiber, basalt fiber, etc. However, the alkali resistance of the slag fiber limits its further application in cement-based materials. Long-term exposure to an alkaline environment can cause the fiber to be corroded, thereby reducing its bonding ability with the matrix material.

[0014] Nanosilica sol is a dispersion of nano-SiO2 particles in water. The particle surface contains silanol groups (‒SiOH) and hydroxyl groups (‒OH), and has advantages such as high activity, good dispersibility, high adsorption capacity, and strong corrosion resistance. In the present invention, nanosilica sol is used to modify the slag fiber, and the modified slag fiber is used as a reinforcement to be mixed with the cement paste, giving full play to its synergistic reinforcement effect of enhancing the cement material and protecting the fiber surface. It can not only improve the workability of the mortar but also increase its mechanical strength. At the same time, a large number of sheet-like calcium silicate hydrate (C‒S‒H) gels are formed on the fiber surface, protecting the basic morphology of the slag fiber in a strong alkaline environment, improving the alkali resistance of the slag fiber, and further enhancing the various properties of the cement mortar. In summary, the modified slag fiber-reinforced cement mortar proposed in the present invention has high strength and crack resistance, and has good technical, economic, and environmental advantages, with broad prospects for popularization and application.

[0015] Compared with the prior art, the present invention has the following advantages: The present invention uses slag fiber as a reinforcement, effectively utilizing solid waste. At the same time, the modified slag fiber-reinforced cement-based material overcomes the problems of low tensile strength, poor early strength, and obvious dry shrinkage cracking of traditional cement-based materials. The present invention can significantly improve the flexural strength and splitting tensile strength of the cement-based material. Among them, the flexural strength at 28 d age is increased by 24.5%, and the splitting tensile strength is increased by 33.8%, improving the toughness of the cement-based material and providing a theoretical basis for its application in engineering. Description of the Drawings

[0016] Figure 1 is the polycondensation reaction of nanosilica sol; Figure 2 is the setting time of the mortar; Figure 3 is the fluidity of the mortar; Figure 4 is the flexural strength of the mortar specimens at 3 d, 7 d, and 28 d; Figure 5 is the compressive strength of the mortar specimens at 3 d, 7 d, and 28 d; Figure 6is the flexural-compressive ratio of the mechanical strength of the mortar specimen; Figure 7 are the cube splitting tensile strengths of the mortar specimens at 3 d, 7 d, and 28 d; Figure 8 is the heat release rate of the neat paste; Figure 9 is the cumulative heat release of the neat paste; Figure 10 are the microtopographies (at 28 d) of the cross-section of the mortar specimen before and after fiber modification. Specific embodiments

[0017] The present invention provides a modified slag fiber reinforced cement mortar and a preparation method thereof. The modified slag fiber reinforced cement mortar is composed of nano-silica sol, slag fiber, composite Portland cement (P.C 42.5), standard sand, and water, wherein the modified slag fiber is obtained by modifying the slag fiber with a modifier; wherein the modified slag fiber accounts for 0.3% of the mass of the cement, the modifier is nano-silica sol, and its mass fraction is 10% of the slag fiber; the mass ratio of cement, standard sand, and water is 1﹕0.75﹕0.4; the technical indexes of the slag fiber (provided by Fujian Dehua Dongxinbo New Materials Technology Co., Ltd.) used in the following examples are shown in Table 1.

[0018] Table 1 Technical indexes of slag fiber Example 1 Unmodified slag fiber reinforced cement mortar: The pretreatment process of the unmodified slag fiber is as follows: (1) Utilizing the property that the slag fiber is uniformly dispersed in water, the agglomerated fibers are immersed in water, and a high-speed shear machine (rotation speed 1000 r / min, time 1 min) is used to completely disperse and homogenize the fibers in water. This treatment process can also etch the fiber surface and increase the surface roughness of the fiber without damaging the physical structure of the fiber.

[0019] (2) The uniformly dispersed fibers are spread flat on a sieve, the water is drained off, and the fibers are placed in an oven at 103 °C and dried for 2 h.

[0020] (3) The dried fibers are taken out, sealed and packaged with a vacuum bag for standby, and the unmodified slag fiber is thus obtained.

[0021] Preparation process of unmodified slag fiber reinforced cement mortar: Add pretreated unmodified slag fiber, cement, and standard sand into a cement mortar mixer, dry mix for 2 min to disperse them evenly, then add water and mix for 1 min. The mass fraction ratio of cement, sand, and water is 1﹕0.75﹕0.4, and the slag fiber accounts for 0.3% of the cement mass. Apply machine oil inside the test mold. After the mortar is prepared and formed, it is loaded into the mold brushed with mold release agent in two layers. Each layer is tamped with a trowel and the surface is leveled. After loading, it is placed on a vibrating table and vibrated for 1 min to make the mortar dense, and the mortar around the mold is scraped off. Demold after placing at room temperature for 24 h, and cure in a standard constant temperature and humidity curing box with a relative humidity of 90 ± 5% and a temperature of 20 ± 5 ℃ for 28 d to obtain the unmodified slag fiber reinforced cement mortar specimen.

[0022] Example 2 Modified slag fiber reinforced cement mortar: Preparation process of modified slag fiber: (1) Utilize the characteristic that slag fiber is evenly dispersed in water. Immerse the agglomerated fiber in water, and use a high-speed shearing machine (rotation speed 1000 r / min, time 1 min) to completely disperse and homogenize the fiber in water. This treatment process can also etch the fiber surface and increase the surface roughness of the fiber without damaging the physical structure of the fiber.

[0023] (2) Spread the evenly dispersed fiber on a sieve, drain the water, and place the fiber in an oven at 103 ℃ for 2 h.

[0024] (3) Spread the dried fiber on a tray, take nano-silica sol, and evenly spray the modifier nano-silica sol on the fiber surface with a nano-level atomizing sprayer to ensure full contact between the fiber and the modifier; Place the fiber sprayed with the modifier in an oven at 103 ℃ for 4 h.

[0025] (4) Take out the dried fiber, seal it with a vacuum bag and set it aside for later use to obtain the modified slag fiber.

[0026] Preparation process of modified slag fiber reinforced cement mortar: Add the modified slag fiber, cement and standard sand into a cement mortar mixer, dry mix for 2 min to make them evenly dispersed, and then add water and mix for 1 min. The mass fraction ratio of cement, sand and water is 1﹕0.75﹕0.4, and the modified slag fiber accounts for 0.3% of the mass of cement; Apply machine oil in the test mold. After the mortar is prepared and formed, it is loaded into the mold coated with mold release agent in two layers. Each layer is tamped with a trowel and the surface is leveled. After loading, it is placed on a vibrating table and vibrated for 1 min to make the mortar dense, and the mortar around the mold is scraped off. Demold after placing at room temperature for 24 h, and cure in a standard constant temperature and humidity curing box with a relative humidity of 90±5% and a temperature of 20±5 ℃ for 28 d to obtain the modified slag fiber reinforced cement mortar specimen.

[0027] Control group (without adding slag fiber) Preparation process of cement mortar: Add cement and standard sand into a cement mortar mixer, dry mix for 2 min to make them evenly dispersed, and then add water and mix for 1 min. The mass fraction ratio of cement, sand and water is 1﹕0.75﹕0.4; Apply machine oil in the test mold. After the mortar is prepared and formed, it is loaded into the mold coated with mold release agent in two layers. Each layer is tamped with a trowel and the surface is leveled. After loading, it is placed on a vibrating table and vibrated for 1 min to make the mortar dense, and the mortar around the mold is scraped off. Demold after placing at room temperature for 24 h, and cure in a standard constant temperature and humidity curing box with a relative humidity of 90±5% and a temperature of 20±5 ℃ for 28 d to obtain the cement mortar specimen.

[0028] Test method (1) The setting time is carried out according to the relevant experimental steps of "Test Methods for Water Requirement of Normal Consistency, Setting Time and Soundness of Cement" (GB / T 1346−2011), and tested with an NLD−3 type Vicat apparatus produced by Wuxi Zhongke Building Materials Instrument Co., Ltd.

[0029] (2) The fluidity is tested with reference to the relevant experimental steps of "Test Method for Fluidity of Cement Mortar" (GB / T 2419−2005). The mortar jump table test is completed within the specified time, and the average diameter of the bottom surface of the mortar on the disc is recorded. Test with an NLD−3 type cement mortar fluidity tester produced by Wuxi Jianyi Instrument Machinery Co., Ltd.

[0030] (3)The automatic flexural and compressive strength testing machine (model YAW−300C) produced by Jinan Orient Test Instrument Co., Ltd. was used to test the flexural strength and compressive strength of the specimens. The test method was in accordance with "Test Method for Strength of Cement Mortar (ISO)" (GB / T 17671−2021). The flexural strength was tested using rectangular parallelepiped specimens with dimensions of 40 mm×40 mm×160 mm. For each group, more than 3 specimens were tested. For the compressive strength, the specimens after breaking were used, and the test area was 40 mm 2 . For each group, more than 6 specimens were tested. After screening out the data with excessive errors, the average value was taken. The test ages were 3 d, 7 d, and 28 d respectively.

[0031] (4)A hydraulic universal testing machine (model YAW−4206) of MTS Industrial Systems (China) Co., Ltd. was used to test the splitting tensile strength of the specimens, referring to "Test Regulations for Cement and Cement Concrete in Highway Engineering" (JTG 3420−2020). The specimen size was a cube with dimensions of 70.7 mm×70.7 mm×70.7 mm. The test ages were 3 d, 7 d, and 28 d respectively. The splitting tensile strength was calculated according to Equation 1: In the formula, f ts represents the splitting tensile strength (MPa); P represents the failure load (N); A represents the splitting surface area of the specimen (mm 2 ). For each test group, 3 specimens were tested. The results were accurate to 0.01 MPa to ensure the stability and reliability of the data. After excluding the data with excessive errors, the average value was taken.

[0032] (5)Scanning electronic microscopy (SEM) is a testing method for characterizing the microscopic morphology of substances. The ZEISS Gemini 300 type emission scanning electron microscope manufactured by Carl Zeiss AG of Germany was used to take pictures of the microscopic morphology of the specimens. The acceleration voltage was 3 kV. Before taking pictures, 28-d compressive specimens were taken, and the specimens were immersed in ethanol solution to completely stop their hydration. Before testing, they were dried and evacuated, and then the specimens were sputter-coated with gold using a sputter coater. The sputter coating target was platinum.

[0033] Test results (1)Setting time ( Figure 2): At the same slag fiber dosage, in Example 2, the fibers were modified with nano-silica sol. Compared with Example 1, the initial setting time was shortened by 14.8% and the final setting time was shortened by 13.6%. Compared with the comparative example, the initial setting time was shortened by 23.2% and the final setting time was shortened by 23.4%. When the dosage of unmodified slag fiber was 0.3%, compared with the comparative example (without adding slag fiber), the initial setting time was shortened by 9.9% and the final setting time was shortened by 11.3%.

[0034] (2) Mortar fluidity ( Figure 3 ): At the same fiber dosage, in Example 2, the fibers were modified with nano-silica sol. Compared with Example 1, the fluidity decreased by 13.3%. Compared with the comparative example, the fluidity decreased by 22.1%. When the dosage of unmodified slag fiber was 0.3%, compared with the comparative example (without adding slag fiber), the fluidity decreased by 10.2%.

[0035] (3) Mortar mechanical properties ( Figure 4 、 Figure 5 ) In terms of flexural strength ( Figure 4 ), for the slag fibers modified with nano-silica sol, the flexural strength of the cement mortar was significantly improved. At the ages of 3 d, 7 d and 28 d, the flexural strength increased by 23.7%, 29.6% and 24.5% respectively compared with that of the comparative example. The highest flexural strength at the 3 d age could reach 7.57 MPa (Example 2); compared with Example 1, the flexural strength of Example 2 at 3 d, 7 d and 28 d increased by 9.0%, 18.8% and 8.1% respectively. In terms of compressive strength ( Figure 5 ), for the slag fibers modified with nano-silica sol, it had an obvious influence on the early compressive strength of the cement mortar. The highest compressive strength at the 3 d age could reach 41 MPa (Example 2); compared with the comparative example, the compressive strength of Example 2 at 3 d and 7 d increased by 10.0% and 15.5% respectively; at the 28 d age, as the hydration of the cement gradually became complete, there was no obvious difference in the compressive strength between Example 2 and the comparative example and Example 1. From the analysis of compressive strength, the improvement effect of its early mechanical properties was more significant. This was mainly because the nano-silica sol particles modified the slag fibers to provide more nucleation sites around the fibers, and more hydration products could be generated in the early stage, promoting the hydration rate, increasing the total amount of heat released by hydration, and promoting more complete hydration (see heat of hydration, Figure 8 、 Figure 9 ). In terms of the flexural-compressive ratio ( Figure 6), the flexural-compressive ratio of the comparative examples and the examples gradually decreased with the increase of the age. This is mainly because the late increase in compressive strength is much higher than that of flexural strength, which conforms to the basic development law of cement-based materials. The flexural-compressive ratio reflects the brittleness of the material (related to the bond between the paste and the aggregate and the generation and development rate of matrix cracks). The smaller the flexural-compressive ratio, the greater the brittleness. The flexural-compressive ratio of Example 2 was the largest at each age, indicating that the modification of slag fibers by nano-silica sol can reduce the brittleness of cement mortar. In terms of splitting tensile strength ( Figure 7 ), the slag fibers modified by nano-silica sol had a significant improvement effect on the splitting tensile strength of cement mortar. At the ages of 3 d, 7 d, and 28 d, the splitting tensile strength of Example 2 was increased by 18.5%, 34.8%, and 33.8% respectively compared with the comparative example.

[0036] (4) Heat of hydration: The appearance time of the induction period of the hydration reaction in Example 2 was slightly shortened. The peak value of its first peak was increased by 16.4% compared with the comparative example. At the same time, the peak value of the second exothermic peak was 3.0% higher than that of the first exothermic peak, indicating that the modification of slag fibers by nano-silica sol promoted the secondary hydration process of cement. And the cumulative heat release of Example 2 was the highest among the three groups. The main reason is that nano-silica has a catalytic effect on the pozzolanic reaction, which promotes the enhancement of the hydration reaction. Its high specific surface area and the presence of hydroxyl active sites on the surface can react with the cement hydration product Ca(OH)2 in the pozzolanic reaction. This reaction consumes Ca(OH)2 and generates additional C−S−H gel.

[0037] (5) Microscopic morphology-energy spectrum scanning ( Figure 10 ): It can be observed that the corrosion degree of the surface of the unmodified slag fibers in Example 1 inside the cement paste and there are many voids between the fibers and the paste. A certain degree of corrosion causes a decrease in the strength of the fiber itself. And when the hydration is completed, with the increase of the corrosion degree of the fiber, the bonding effect between the fiber and the paste will be reduced, weakening the interfacial transition zone between the two. In Example 2, it can be observed that evenly distributed C−S−H gels are adhered to its surface and around, and the corrosion degree of the fiber surface is significantly lower than that of Example 1. The fiber shape is basically complete in the matrix material, which proves that there is a better interfacial bond between the modified slag fiber and the paste.

[0038] The above is only the preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, all equivalent changes and modifications made according to the scope of the patent application of the present invention shall fall within the scope covered by the present invention.

Claims

1. A modified slag fiber reinforced cement mortar, characterized in that: The raw material composition of the modified slag fiber reinforced cement mortar includes modified slag fibers, cement, standard sand and water, where the modified slag fibers are obtained by modifying slag fibers with a modifier; the modified slag fibers account for 0.3% of the mass of the cement, and the modifier is nano-silica sol, and its mass fraction is 10% of the slag fibers; the mass ratio of cement, standard sand and water is 1:0.75:0.4; The preparation method of the modified slag fibers includes the following steps: (1) Utilizing the property that slag fibers are uniformly dispersed in water, the agglomerated slag fibers are immersed in water, and a high-speed shear machine is used to completely disperse and homogenize the slag fibers in water. This treatment process can also etch the surface of the slag fibers, increasing the surface roughness of the slag fibers without damaging the physical structure of the slag fibers; (2) The uniformly dispersed slag fibers are spread out on a sieve, the water is drained off, and the slag fibers are placed in an oven at 103 °C for drying for 2 h; (3) The dried slag fibers are spread out on a tray, nano-silica sol is taken, and the modifier nano-silica sol is evenly sprayed on the surface of the slag fibers with a nano-level atomizing sprayer to ensure full contact between the slag fibers and the modifier; the slag fibers sprayed with the modifier are placed in an oven at 103 °C for drying for 4 h to obtain the modified slag fibers.

2. The modified slag fiber reinforced cement mortar according to claim 1, characterized in that: The nano-silica sol is a transparent liquid, with the solid content of SiO2: 30 ± 1 wt%, the solid content of Na2O: ≤ 0.3 wt%, and its physical property indexes are viscosity: 7 mPa.s, density: 1.21~1.29 g / cm 3 , particle size: 10~20 nm, pH value: 9~10.

3. The modified slag fiber reinforced cement mortar according to claim 1, characterized in that: The length of the slag fibers is 3.9 - 5 mm, and the diameter is 900 - 950 μm.

4. The modified slag fiber reinforced cement mortar according to claim 1, characterized in that: The particle size of the standard sand is 0.08 - 1.6 mm.

5. The modified slag fiber reinforced cement mortar according to claim 1, wherein: The cement is composite Portland cement P.C 42.

5.

6. The modified slag fiber reinforced cement mortar according to claim 1, wherein: In step (1), the rotation speed of the high-speed shear machine is 500 - 1000 r / min, and the treatment time is 1 - 3 min.

7. The preparation method of the modified slag fiber reinforced cement mortar according to claim 1, wherein: It includes the following steps: The modified slag fibers, cement and standard sand are mixed in proportion, dry-mixed for 2 - 3 min, uniformly stirred and then water is added and stirring continues for 1 min, and then manually tamped and placed on a vibrating table for vibration molding; after solidifying for 24 h, demolding is carried out, and the specimens are placed in a standard constant temperature and humidity curing box for curing to obtain the modified slag fiber reinforced cement mortar specimens.

8. The preparation method according to claim 7, wherein: The specific operation of curing in the standard constant temperature and humidity curing box includes: curing in a standard constant temperature and humidity curing box at a relative humidity of 90 ± 5% and a temperature of 20 ± 5 °C for 28 d.

Citation Information

Cited By

  • Preparation process of high-strength cement-based mine filling material containing modified muck

    CN122380761A

  • Preparation process of a high-strength cement-based mine backfill material containing modified slag soil

    CN122380761B